Compliant Yet Brittle Mechanical Behavior of Li2S–P2S5 Lithium‐Ion‐Conducting Solid Electrolyte. Issue 12 (30th January 2017) - McGrogan, Frank P.; Swamy, Tushar; Bishop, Sean R.; Eggleton, Erica; Porz, Lukas; Chen, Xinwei; Chiang, Yet‐Ming; Van Vliet, Krystyn J.
Abstract : Young's modulus, hardness, and fracture toughness are measured by instrumented nanoindentation for an amorphous Li2 S–P2 S5 Li‐ion solid electrolyte. Although low elastic modulus suggests accommodation of significant chemomechanical strain, low fracture toughness can facilitate brittle crack formation in such materials.